The influence of accounting students’ personality traits toward their entrepreneurship intention - Ahmad, Noor Lela; Fazil, Nadiah Farhanah Mohd; Yusof, Rohaila; Jamaluddin, Nor Sa’adah; Yahaya, Rusliza (Institute of Advanced Engineering and Science, 2024)
This paper intends to explore entrepreneurship intention among the youth by examining their personality traits. The respondents of this study were accounting students in their final year from seven public universities across Malaysia. A validated questionnaire was employed and distributed to representatives of each university, obtaining a total of 756 responses. The collected data was analyzed using descriptive statistics and utilized partial least square-structural equation modelling (PLS-SEM) to analyze the hypotheses. The results revealed that personality traits influence entrepreneurship intention of accounting students’ and conscientiousness being the most significant trait with a coefficient of 0.612. This paper suggests that personality traits namely conscientiousness, extraversion, openness to experience and agreeableness can boost entrepreneurship attitude, thus it should be optimized systematically into the education context to shape young personalities that are inclined towards entrepreneurship. Essentially, Ministry of Higher Institution, universities, colleges, and schools are advised to shape entrepreneurial personalities through the education curriculum and frequent practical sessions with inspiring entrepreneurs in the industry. Further, integrating the elements of personality traits into entrepreneurship education can serve as a guide for financial management of a business.